Capture of Leucoptera coffeella (Lepidoptera: Lyonetiidae) in sex pheromone traps and damage intensity - BACCA, TITO; SARAIVA, RODRIGO M.; LIMA, ERALDO R. (Revista Colombiana de Entomología, 2012)
The use of pheromone traps was tested for monitoring males of the coffee leaf miner, Leucoptera coffeella (Guérin-Méneville) (Lepidoptera: Lyonetiidae). Insect sampling was carried out in seven coffee plantations under dif- ferent agronomic conditions in the two regions - Triângulo Mineiro and Zona da Mata, MG, Brazil. The sampling period ranged from 6 to 20 months. The locality significantly affected male capture. Among the weather variables analyzed, the decrease in the average temperature favored higher infestations of L. coffeella in coffee plants and higher male capture. A positive relation between male capture and percent of leaves mined (R2 = 0.79) was observed in the Triângulo Mineiro while in Zona da Mata this relationship was weak, although significant (R2 =0.06). In this last region, a positive and significant correlation between males captured and pest eggs was observed (R2 = 0.34). The results of this study suggest that there is a significant correlation between the male capture by pheromone traps and the population density of L. cof- feella, emphasizing the potential of pheromone traps for monitoring the coffee leaf miner.